Identifikasi Staphylococcus Aureus pada Abon Ikan Pangan Industri Rumah Tangga - Ulfah Hamdan; Rupaida Oktafia; Muriany Faisal; Irda Rezkina Azis (Indonesian Journal of Fundamental Sciences, 2026)
Abstract. This study aimed to identify the presence of Staphylococcus aureus in fish floss products produced by Home Industry Food Enterprises (PIRT) distributed in Makassar City and evaluate their compliance with microbiological safety standards. A descriptive retrospective study was conducted using secondary microbiological testing data from the Center for Drug and Food Control (BBPOM) in Makassar during May–September 2025. A total of 10 registered PIRT fish floss samples were analyzed using the ISO 6888-1 method for the detection of coagulase-positive Staphylococcus aureus. The results showed that no Staphylococcus aureus contamination was detected in any sample, and all products complied with the microbiological safety requirements established by BPOM Regulation No. 13 of 2019. These findings indicate that the evaluated PIRT fish floss products fulfilled microbiological safety criteria for the Staphylococcus aureus parameter.Keywords: Fish Floss; PIRT; Staphylococcus aureus; Makassar City; ISO 6888-1